Tunable focus lens using electroactive polymer - Ng, Sylvester Aik Tong (2017)
Lenses have been around for centuries, with vast applications in telescopic and microscopic fields. As the demand for smaller and compact technology increases, new technologies converting conventional bigger lenses into lightweight and condensed forms have surfaced, one of the prevailing technologies today being the Dielectric Elastomer Actuator (DEA) Tuneable Lens. However this type of Tuneable Lens is faced with limited Focal Length range and requires high Voltage for actuation. This thesis is designed to address the issues of the DEA Tuneable Lens deforming in high Voltage actuation. By introducing cured Gel lens as a solid encapsulation replacement for the current Oil lens, the experiment hypothesizes that increasing the stiffness of the lens will reduce chances of deformation from high Voltage actuation. In this experiment, two encapsulation materials, the conventional Oil lens and the Gel lens undergo identical high Voltage actuation respectively to test for deformation. The performances of both of the lens were then tested for their Radius of Curvature and Focal Length against the activation Voltage. The primary results derived from the experiments reveal that the Oil encapsulation showed signs of deformation when placed under high activation Voltage of about 6kV. On the other hand, the cured Gel encapsulation successfully maintained the shape of the lens. The difference in ability to retain the lens structure is attributed to the stiffness of the Gel Lens .These findings have significant implications for the commercial application of tuneable lens.